Information Warfare Tactics and Techniques - Groš, Stjepan (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
Information warfare, disinformation, fake news, and similar terms are frequently used in public discourse. It is clear from real-world examples that these concepts represent a substantial danger for democratic countries, polarise societies as regards public health, and generally prevent rational and informed discussion. Yet, combating disinformation proves very difficult. Something must be done, but the question is what. The premise of this chapter is that we cannot counter disinformation if we do not agree on what we are fighting against; that is, we cannot do something if we do not know what the adversaries are using against us. In cybersecurity, databases of tactics and techniques of adversaries’ behaviour have proved very useful for defence. Knowing about different types of attackers, their motives, and capabilities has also proved beneficial. Therefore, we are set to replicate this success in the case of information warfare and information operations. To achieve these goals, we review the terminology and define information warfare in a narrow sense and then discuss information operations, their relation to military domains and information space, and the domains in which information operations are run. In doing so, we determine that information operations are intertwined with and appear in all military domains. The core part of this chapter lists the tactics and techniques adversaries use for information operations. We then review the logistics support adversaries might use for information operations; moreover, we define threat sources and threat actors and classify them based on their motivations and capabilities. Finally, we map the operations run during Operation Denver to the tactics and techniques presented in this chapter to illustrate their use.Keywords: warfare, information warfare, information operations, cyber warfare, tactics, technics, procedures, mitre att&ck, operation Denver